Polyacetylene From Dendropanax morbifera Alleviates Diet-Induced Obesity and Hepatic Steatosis by Activating AMPK Signaling Pathway - Kang, Myung-Ji; Kwon, Eun-Bin; Ryu, Hyung Won; Lee, Seoghyun; Lee, Jae-Won; Kim, Doo-Young; Lee, Mi Kyeong; Oh, Sei-Ryang; Lee, Hyun-Sun; Lee, Su Ui; Kim, Mun-Ock (Frontiers in Pharmacology, 2018)
The extract tea of Dendropanax marbifera is popular beverages in Korea, and their preventive and therapeutic roles in metabolic disorders have been reported. However, the molecular mechanism has not been studied despite the known efficacy of D. morbifera. Eleven fractions (fr.1-fr.11) were divided by MPLC to find the active compound. Among them, Fr.5 was superior to others in that the inhibitory efficacy of de novo triglyceride (TG) biosynthesis. NMR analysis revealed that Fr.5 is composed 98% or more (9Z, 16S)-16-hydroxy-9, 17-octadecadiene-12, 14-diynoic acid (HOD). Treatment of HOD diminished oleic acid (OA)-induced TG accumulation in HepG2 hepatocytes and differentiation of 3T3-L1 preadipocytes by activating LKB1/AMPK. In addition, we determined the effect of the oral administration of the extract of D. morbifera on obesity and hepatic steatosis in high-fat diet (HFD)-induced obese mice. This study proved that D. morbifera containing HOD, the active substance, can show preventive or therapeutic efficacy on obesity and hepatic steatosis through the targeting LKB1/AMPK axis.